Analisis Kemampuan Penalaran Matematis Siswa dalam Pembelajaran Online Learning System SD Negeri Kutabumi II - Atiyah, Ummi; Mawardi, Mawardi; Hasan, Najib (Lembaga Yasin AlSys, 2021)
This research is based on researchers' concerns about students' mathematical reasoning abilities in online learning during the covid 19 pandemic. It was said in previous research that students' mathematical reasoning abilities were still below average. The purpose of this research is to describe students' mathematical reasoning abilities in online learning in solving mathematical problems in elementary students. The research method used is qualitative research with descriptive methods. The subjects in this study were two fifth grade students at SD Negeri Kutabumi II. The instruments in this study were observation, tests, interviews and documentation. The results showed that the students' mathematical reasoning ability in online learning was still low, with an average value of 45.6%. Of the 4 assessment indicators (1) submit conjectures, (2) perform mathematical manipulation, (3) provide conclusions, compile evidence, provide reasons or evidence for several solutions (4) provide validity of the statement. Subjects have difficulty in indicators 3 and 4 so they cannot solve the questions given properly and correctly.